Obesity in Pregnancy and Childbirth. Issue 6 (November 2021) - Killion, Molly M.
Abstract : Rates of pre-pregnancy obesity in the United States have increased significantly over the last several years. Obesity increases risk of adverse pregnancy outcomes. Our maternity nursing expert, Molly Killion, reviews the most recent data on obesity and recommendations for clinical care.